BALTEX water and energy budgets in the NCEP/DOE reanalysis II - Roads, J.; Raschke, E.; Rockel, B. (Boreal Environment Research Publishing Board, 2024)
Water and energy budgets from the National Centers for Environmental Prediction/Dept. of Energy (NCEP/DOE) reanalysis II (NCEPRII) are described for the Baltic Sea catchment and sea (BALTEX). Annually, NCEPRII shows 0.7 mm d–1 of atmospheric moisture converged into the land region with a corresponding runoff of 0.7 mm d–1 to the Baltic Sea, consistent with observations. However, precipitation is too low; evaporation is too large; runoff does not have an appropriate winter minimum and spring maximum; the assimilation and surface nudging are too large. Important hydroclimatic characteristics can still be discerned. During summer, atmospheric water vapor, precipitation, evaporation, and surface and atmospheric radiative heating increase and the atmospheric radiative cooling, dry static energy convergence decrease. There are large contrasts between the sea and land; during winter sensible heat is transferred from the sea to the atmosphere and sea evaporation and precipitation are largest during the fall and winter; somewhat opposite behavior occurs over land.